Review of implementation of rigid pavemant cement clamping work on the reconstruction of the road access to Tol Palaran - Putri, Pooja Hemalia; Agustina, Fitriyati; Ardian, Yuli Arianto (LPPI Universitas Muhammadiyah Kalimantan Timur (UMKT), 2024)
The East Kalimantan Provincial Government carried out reconstruction work on the Palaran Toll access road (Palaran Main Stadium). This work is very strategic considering that the route is one of the accesses to national vital objects (obvitnas) of the Samarinda - Balikpapan Toll Road. In addition to providing comfort for road users, the path will be a storefront for Samarinda City. This path will be an access in and out of and to the Palaran Toll Gate. Previously, the two-lane road section was only used for one lane on the right side of the Palaran Main Stadium. The lane was partially destroyed, scrubbed and only became a parking office for trucks and containers. But considering that this road is a provincial road, the existing road conditions are considered unable to accommodate the capacity of vehicles going through this route. So it is necessary to rebuild and improve roads on the East Kalimantan Main Stadium Road Section at Sta. 1+644 – Sta. 3+405 to facilitate economic traffic and also avoid traffic accidents in the area. The methods used to obtain data are direct observation methods of activities that occur in the field and secondary data collection in the form of test result data, and work plan drawings. The purpose of writing this article is to find out the stages of implementation and supervision of cement concrete pavement road work, especially in ironing work. Palaran Toll Access Road Reconstruction Project using iron 32 mm for dowel rods with a length of 450 mm and a distance of 300 mm, iron 16 mm for tie bars with a length of 700 mm and a distance of 750 mm, as well as iron 12 mm for dowel fulcrum reinforcement and tie bar.